Multiple sclerosis with megacystic presentation: A case report - Andrés Felipe Herrera Ortiz, MD; Santiago Aristizabal, MD; Juan Guillermo Arámbula, MD; Valeria del Castillo, MD; Juan Calderon, MD; Nury Tatiana Rincón Cuenca, MD; María José Abuchar, MD; María Mónica Yepes, MD; Angela Guarnizo, MD (Radiology Case Reports, 2023)
Multiple sclerosis is a frequent condition where the diagnosis relies on clinical presentation, neurologic examination, cerebro spinal fluid markers, and diagnostic imaging tests; however, atypical variants of the disease can lead to misdiagnosis in some scenarios. Herein, we describe a case of a 24-year-old patient with multiple sclerosis with megacystic plaques, in which appropriate interpretation of the imaging findings lead to a proper diagnosis and treatment.